URINARY TRACT INFECTION OF PATIENTS WHO TREATED IN HOSPITAL - Indrawan, Desta Eko (Majority, 2015)
Abstrack Nosocomial infections are still a serious problem in developing countries. WHO said that, nosocomial infections cause 1.4 million deaths in worldwide each day. A place that has the potential to be a source of transmission of nosocomial infections are hospital. Hospitals as providers of health facilities also become a meeting place for the sick and healthy people, so it can be potential source of nosocomial transmission infection. The various types of nosocomial infections, most often found in patients whose hospitalized is a urinary tract infection. Urinary tract infections can caused by bacteria, viruses and fungi with most common causing bacteria is Escherichia coli. Urinary tract infections diagnose can be enforced if we found > 105 CFU bacteria/ml of urine. UTI in patients who treated in the hospital can be caused by contact with non-sterile equipment or through cross-contamination from hand contact by patients or hospital personnel. beside that, other factors such as environment, duration of hospitalization, and usie invasive tools such as catheter can also increase the risk of urinary track infection. Keyword : hospital, nosocomial infection, urinary track infection. Abstrak Infeksi nosokomial hingga saat ini masih merupakan masalah yang cukup serius pada negara berkembang. WHO menyebutkan, infeksi nosokomial menyebabkan 1,4 juta kematian setiap hari di seluruh dunia. Salah satu tempat yang berpotensi menjadi sumber penularan infeksi nosokomial adalah rumah sakit. Rumah sakit sebagai pemberi sarana kesehatan juga menjadi tempat bertemunya orang sakit dengan orang sehat sehingga menjadi tempat yang berpotensi menjadi sumber penularan infeksi nosokomial. Dari berbagai jenis infeksi nosokomial, yang paling sering ditemukan pada pasien yang di rawat dirumah sakit adalah infeksi saluran kemih. Infeksi saluran kemih dapat disebabkan oleh bakteri, virus dan jamur dengan bakteri penyebab tersering adalah Escherichia coli. Diagnosa Infeksi saluran kemih dapat ditegakkan apabila ditemukan adanya bakteri >105 CFU/ml urin. Tejadinya ISK pada pasien yang di rawat di rumah sakit dapat disebabkan oleh kontak dengan peralatan yang tidak steril atau melalui kontaminasi silang dari kontak tangan oleh pasien atau petugas rumah sakit. Selain itu faktor-faktor lain seperti lingkungan, lama masa rawat, dan penggunaan alat invasif seperti kateter juga dapat meningkatkan risiko terjadinya infeksi saluran kemih. Kata kunci : Infeksi nosokomial, infeksi saluran kemih, rumah sakit